Establishing Priorities for the International Confederation of Plastic Surgery Societies. Issue 9 (September 2018) - Cooter, Rodney D.; Brightman, Louise A.; Clarke, Howard M.; Cruz, Norma I.; Evans, Greg R. D.; Koh, Kyung S.; Murphy, Robert X.; Perks, Graeme A. B.; Rakhorst, Hinne A.
Abstract : Background: The mission of the International Confederation of Plastic Surgery Societies (ICOPLAST) is to improve patient outcomes through collaboratively structured processes in education, advocacy and communication. This article explains how we approached the task of establishing priorities for this nascent confederation in an equitable and achievable manner. Methods: In late 2016, an online survey was sent to the inaugural 62 ICOPLAST member national societies for dissemination to their respective plastic surgeon members. Functional domains and proposed initiatives were ranked according to their level of importance by individual plastic surgeons. Results: The survey was completed by 572 plastic surgeons. As a functional domain, education was highly ranked by 75.3% of respondents, followed by patient safety (67.4%), communication (59.3%), humanitarian (46.6%), regulation (41.2%), and advocacy (41.1%). Respondents also ranked individual initiatives within each domain to produce a compilation list of the top 13 initiatives of importance. Conclusion: This study has identified priorities of importance to ICOPLAST members, which will aid in building a strategic framework and enhancing outcomes for patients, plastic surgeons, and the field of plastic surgery more broadly. Abstract : Supplemental Digital Content is available in the text.